Pengolahan Sosis dari Jamur Sawit sebagai Upaya Diversifikasi Olahan Pangan Di Desa Pondok Kubang Kabupaten Bengkulu Tengah - Putri, Welin Camelia; Satriawan, Mugianto; Permata, Lusita Dian; Rohim, Ahmad (Jurnal Dehasen Mengabdi, 2025)
Pondok Kubang Village is a village whose majority of people work as oil palm farmers. Oil palm plants that grow in the community's gardens produce good quality fruit because the community routinely fertilizes the gardens with natural fertilizers such as TKKS or better known as jangkos. The piles of TKKS in the garden produce oil palm mushrooms that can be consumed, but the community still does not utilize oil palm mushrooms optimally. Based on the results of the survey and socialization with the local community, community service was carried out by students in Pondok Kubang Village. The purpose of this service is to increase public awareness of the benefits of oil palm mushrooms and to make oil palm mushrooms a new product that will increase economic value. Making oil palm mushroom sausage is quite simple because the ingredients used are easy to obtain and of course more economical. The resulting oil palm mushroom sausage can be a food that is popular with all groups. In addition, PKK mothers who are involved in making oil palm mushroom sausages can use this knowledge as a basis for starting a business.